Phosphorus migration from sediment to phosphorus-inactivating material: A key process neglected by common phosphorus immobilization assessments for lake geoengineering - Changhui Wang; Xinyi Shen; Bo Fan; Wei Huang; Chenghao Huang; Leilei Bai; Helong Jiang (Water Research X, 2023)
Various phosphorus (P)-inactivating materials with a strong capability of immobilizing P in sediment have been developed for lake geoengineering purposes to control internal P pollution. However, unsatisfactory applications have raised concerns about the reliability of the method. This study hypothesized that P migration from sediment to material is a key process regulating the immobilization, which is often neglected by common assessment procedures that assume that the material is closely in contact with sediment (e.g., as mixtures). To verify this hypothesis, 90-day incubation tests were conducted using drinking water treatment residue (DWTR). The results showed that the soluble P in the overlying water of sediment–DWTR mixtures and the mobile P in the mixtures were substantially reduced from the initial period and remained low during the whole incubation tests. However, assessment based on separated samples indicated a gradual P migration from sediment to DWTR for immobilization. Even after 90 days of incubation, mobile P still accounted for ∼5.33% of total P in the separated sediment. Further analysis suggested that using mixtures of sediment with DWTR accelerated P migration during the assessment, leading to a faster P immobilization assessment. Considering the relatively low levels of mobile P in the separated DWTR during incubation, the gradual decrease in mobile P in the separated sediment indicates that sediment P release regulates P immobilization efficiency. Therefore, designing a proper strategy to ensure sufficient time for the material to remain in close contact with the target sediment is critical to reducing uncertainties in lake geoengineering.